Metal composite film and lithium ion battery
By using an inner bonding layer of organic fluororesin and acid modified polypropylene in lithium-ion batteries, combined with the addition reaction of an epoxy-based curing agent and a catalyst, the inner bonding liquid in the prior art has been solved. The problem of insufficient performance at high temperatures has achieved rapid maturation and efficient cross-linking of metal composite films, improving the corrosion resistance and safety of lithium-ion batteries.
Patent Information
- Application Number
- CN202411255164.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The inner bonding liquid of existing soft-pack lithium-ion batteries does not have sufficient high temperature resistance, corrosion resistance, durability and safety performance under high temperature conditions. It has risks of electrolyte swelling, penetration and air cracking, making it difficult to ensure electrochemical performance. and use safety.
The inner bonding layer is adopted which includes organic fluororesin, acid modified polypropylene, epoxy curing agent, isocyanate curing agent, special amine catalyst, amidine nitrogen-containing organic substance and imidazole-type epoxy resin combined with octanoate. The cross-linking curing is strengthened through addition reaction, and the metal composite film formed is mainly epoxy-based curing agent and catalyst, which reduces the maturation time and increases the binding strength.
The rapid maturation of metal composite film has been achieved, and the corrosion resistance, packaging properties, high temperature resistance, durability and electrochemical reaction stability have been improved, and the penetration and leakage of electrolytes have been avoided, ensuring the safety of lithium-ion batteries and Stable performance.
Smart Images

Figure CN119119894A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a battery packaging material, in particular to a metal composite film suitable for soft-package lithium-ion batteries. Background Art
[0002] Due to the rapid development of the new energy industry, the requirements for high temperature resistance, corrosion resistance, durability, and safety performance of the outer packaging materials in the field of soft-pack batteries are gradually increasing. Among them: the inner adhesive layer is a medium used to connect the intermediate metal layer and the hot-melt resin layer to prevent the two from peeling off from each other, and to avoid the electrolyte from penetrating into each layer during the battery charging and discharging process, which may cause safety hazards. The inner adhesive liquid currently used in the industry is mainly composed of polypropylene, so it usually needs to be matured at a temperature of 80°C for 5 to 7 days to complete cross-linking and curing. However, after the aging is completed, the obtained metal composite film is not sufficient in terms of high temperature resistance, corrosion resistance, durability, and safety performance, and there is a risk of electrolyte swelling, electrolyte penetration, or bulging cracking. In view of the above problems, it is necessary to provide a battery packaging structure that can be quickly matured and ensure the electrochemical performance and safety of the battery. Summary of the invention
[0003] The object of the present invention is to provide a battery packaging structure that can be rapidly aged and ensure the electrochemical performance and safety of the battery.
[0004] To achieve the above-mentioned purpose, the present invention provides a metal composite film, characterized in that it includes: an intermediate metal layer; an inner bonding layer formed on one side of the intermediate metal layer, wherein the inner bonding layer contains: a main agent, including: one or more of organic fluorine resin and acid-modified polypropylene; a curing agent, including: one or more of epoxy curing agent and isocyanate curing agent; and a catalyst, including: one or more of special amine catalysts, amidine nitrogen-containing organic matter, imidazole-type epoxy resin compound octanoate, and organic tin catalyst; and a hot melt resin layer formed on one side of the inner bonding layer, so that the inner bonding layer is located between the intermediate metal layer and the hot melt resin layer.
[0005] More preferably, the curing agent is an epoxy curing agent, and the catalyst is a special amine catalyst; or the curing agent is an epoxy curing agent, and the catalyst is an amidine-type nitrogen-containing organic compound; or the curing agent is an epoxy curing agent, and the catalyst is an imidazole-type epoxy resin compounded with octanoate; or the curing agent is an isocyanate curing agent, and the catalyst is an organic tin catalyst.
[0006] More preferably, the epoxy curing agent is one or more selected from the group consisting of the following materials: bisphenol A epoxy resin, bisphenol F epoxy resin, phenol novolac epoxy resin, o-cresol novolac epoxy resin, trisphenol methane epoxy resin, tetraphenol ethane epoxy resin, polyphenol glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin, and glycidyl ester epoxy resin; the special amine catalyst is one or more selected from the group consisting of the following materials: triethyl methyl ammonium 2- Ethylhexane salt, tetramethylammonium chloride, and triethylenediamine; amidine nitrogen-containing organic matter is one or more selected from the group consisting of the following materials: 1,8-diazabicyclo[5.4.0]undecene-7 phenolate, 1,5-diazabicyclo[4.3.0]non-5-ene, and triazoamidine; imidazole epoxy resin compound octanoate is one or more selected from the group consisting of the following materials: 2-methylimidazole (2MZ), 2-ethyl-4-methylimidazole (2E4MZ), 2-phenyl-4-methylimidazole (2P4MZ), 1-benzyl-2-phenylimidazole (1B2PZ), 2-phenylimidazole (2PZ), 2-undecylimidazole (C11Z), 2-heptadecylimidazole (C17Z), 1-aminoethyl-2-methylimidazole (AMZ), 2-methylimidazole-trimellityl chloride anhydride (2MI-T), and 2-ethyl-4-methylimidazole-trimellityl chloride anhydride (EMI-T); the isocyanate curing agent is selected from the following materials One or more of the group: aliphatic polyisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate; and the organic tin catalyst is one or more selected from the group consisting of the following materials: dibutyltin oxide, dibutyltin dibutyrate, dimethyltin dibutyrate, dioctyltin dibutyrate, dibutyltin diacetate, dimethyltin diacetate, dioctyltin diacetate, dimethyltin dilaurate, dibutyltin dilaurate, stannous octoate, stannous oleate, and dibutyltin didodecylsulfide.
[0007] More preferably, the hydroxyl value of the organic fluorine resin is 20mgoH / g to 80mgoH / g; and / or the weight ratio of the organic fluorine resin to the acid-modified polypropylene is 40:100.
[0008] More preferably, the curing agent is an isocyanate curing agent, and the catalyst is an organic tin catalyst, and: the organic tin catalyst contains dibutyltin dilaurate and stannous octoate in a weight ratio of 7:3; and / or the content of the organic tin catalyst is 0.03 to 0.5wt% based on the total weight of the main agent.
[0009] More preferably, the active temperature of the catalyst is 90°C to 110°C.
[0010] More preferably, the inner adhesive layer is formed by curing the inner adhesive liquid at a temperature of 175° C. to 195° C. for 1 minute.
[0011] More preferably, the curing agent is an epoxy curing agent, and the catalyst includes, based on the total weight of the epoxy curing agent: 8 to 45 wt% of a special amine catalyst, or 8 to 45 wt% of amidine nitrogen-containing organic matter, or 8 to 45 wt% of imidazole epoxy resin compound caprylate.
[0012] More preferably, after the metal composite film is stored in a hot box at 120° C. for 5 minutes, its heat sealing strength is ≥50N.
[0013] More preferably, it further includes: an inner anti-corrosion layer formed between the intermediate metal layer and the inner bonding layer; or an outer anti-corrosion layer formed on one side of the intermediate metal layer, so that the intermediate metal layer is located between the outer anti-corrosion layer and the inner bonding layer; or an outer bonding layer formed on one side of the intermediate metal layer, so that the intermediate metal layer is located between the outer bonding layer and the inner bonding layer; or an outer base resin layer formed on one side of the intermediate metal layer, so that the intermediate metal layer is located between the outer base resin layer and the inner bonding layer.
[0014] The present invention further provides a lithium-ion battery, characterized in that it comprises: a metal composite film, which defines an accommodation space inside to selectively accommodate electrolyte, wherein: the metal composite film comprises: an intermediate metal layer; an inner adhesive layer formed on one side of the intermediate metal layer, wherein the inner adhesive layer comprises: a main agent, comprising: one or more of organic fluorine resin and acid-modified polypropylene; a curing agent, comprising: one or more of epoxy curing agent and isocyanate curing agent; and a catalyst, comprising: one or more of special amine catalysts, amidine nitrogen-containing organic matter, imidazole-type epoxy resin compound octanoate, and organic tin catalyst; and a hot-melt resin layer formed on one side of the inner adhesive layer, so that the inner adhesive layer is located between the intermediate metal layer and the hot-melt resin layer, and the hot-melt resin layer is closer to the accommodation space than the inner adhesive layer. Since the content of this embodiment is roughly the same as the above-mentioned metal composite film, it will not be described in detail here.
[0015] The effectiveness of the present invention relative to the prior art is that the present invention limits the material selection of the main agent, curing agent, and catalyst in the components of the inner adhesive layer, so that an addition reaction occurs between them to strengthen the bonding strength of the cross-linking curing, and greatly reduce the time required for aging to meet the needs of industrial production. In addition, by limiting the components of the inner adhesive layer, the metal composite film provided by the present invention can have excellent corrosion resistance, packaging, high temperature resistance, durability, insulation, electrochemical reaction stability, safety of use, and peel strength, so that during the charging and discharging process of the lithium-ion battery, when the temperature of the battery rises, the metal composite film can still maintain its structural strength without stratification, and avoid electrolyte penetration or leakage. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a plane diagram for illustrating the structural features of the metal composite film;
[0017] Figure 2 is a plane diagram for illustrating the structural features of the metal composite film;
[0018] Figure 3 It is a plan view used to illustrate the structural features of a lithium-ion battery. DETAILED DESCRIPTION
[0019] In order to make the above and / or other purposes, effects, and features of the present invention more clearly understood, preferred embodiments are specifically described below in detail:
[0020] The object of the present invention is to provide a metal composite film 1, wherein Figure 1 As shown, it includes: an intermediate metal layer 2; an inner adhesive layer 3, formed on one side of the intermediate metal layer 2, wherein the inner adhesive layer 3 contains: a main agent, including: one or more of organic fluorine resin and acid-modified polypropylene; a curing agent, including: one or more of epoxy curing agent and isocyanate curing agent; and a catalyst, including: one or more of special amine catalysts, amidine nitrogen-containing organic matter, imidazole epoxy resin compound octanoate, and organic tin catalyst; and a hot-melt resin layer 4, formed on one side of the inner adhesive layer 3, so that the inner adhesive layer 3 is located between the intermediate metal layer 2 and the hot-melt resin layer 4. In a preferred embodiment, the organic fluorine resin is an alternating copolymer of fluoroethylene and vinyl ether, and its hydroxyl value is 20mgoH / g to 80mgoH / g, preferably 60mgoH / g to 80mgoH / g; and / or the weight ratio of the organic fluorine resin to the acid-modified polypropylene is 40:100, but not limited thereto.
[0021] Preferably, in order to improve the packaging, high temperature resistance, corrosion resistance, durability, insulation, electrochemical reaction stability, safety of use, or peel strength of the metal composite film 1, when the temperature of the battery rises during the charging and discharging process of the lithium-ion battery, the metal composite film 1 can still maintain its structural strength without stratification, and avoid electrolyte penetration or leakage, wherein: the curing agent is an epoxy curing agent, and the catalyst is a special amine catalyst; or the curing agent is an epoxy curing agent, and the catalyst is an amidine-type nitrogen-containing organic matter; or the curing agent is an epoxy curing agent, and the catalyst is an imidazole-type epoxy resin compounded with octanoic acid salt; or the curing agent is an isocyanate curing agent, and the catalyst is an organic tin catalyst. Specifically, the epoxy curing agent is one or more selected from the group consisting of the following materials: bisphenol A epoxy resin, bisphenol F epoxy resin, phenol novolac epoxy resin, o-cresol novolac epoxy resin, trisphenol methane epoxy resin, tetraphenol ethane epoxy resin, polyphenol glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin, and glycidyl ester epoxy resin; the special amine catalyst is one or more selected from the group consisting of the following materials: triethyl methyl ammonium 2- Ethylhexane salt, tetramethylammonium chloride, and triethylenediamine; amidine nitrogen-containing organic matter is one or more selected from the group consisting of the following materials: 1,8-diazabicyclo[5.4.0]undecene-7 phenolate, 1,5-diazabicyclo[4.3.0]non-5-ene, and triazoamidine; imidazole epoxy resin compound octanoate is one or more selected from the group consisting of the following materials: 2-methylimidazole (2MZ), 2-ethyl-4-methylimidazole (2E4MZ), 2-phenyl-4-methylimidazole (2P4MZ), 1-benzyl-2-phenylimidazole (1B2PZ), 2-phenylimidazole (2PZ), 2-undecylimidazole (C11Z), 2-heptadecylimidazole (C17Z), 1-aminoethyl-2-methylimidazole (AMZ), 2-methylimidazole-trimellityl chloride anhydride (2MI-T), and 2-ethyl-4-methylimidazole-trimellityl chloride anhydride (EMI-T); the isocyanate curing agent is selected from the following materials One or more of the group: aliphatic polyisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate; and the organic tin catalyst is one or more of the group consisting of the following materials: dibutyltin oxide, dibutyltin dibutyrate, dimethyltin dibutyrate, dioctyltin dibutyrate, dibutyltin diacetate, dimethyltin diacetate, dioctyltin diacetate, dimethyltin dilaurate, dibutyltin dilaurate, stannous octoate, stannous oleate, and di(dodecylsulfide) dibutyltin. Specifically, after the metal composite film 1 is stored in a hot box at 120° C. for 5 minutes, its heat sealing strength is ≥50N.In a preferred embodiment, based on the total weight of the epoxy curing agent, the epoxy curing agent comprises: 90 wt % of bisphenol F epoxy resin and 10 wt % of novolac epoxy resin, but the present invention is not limited thereto.
[0022] More preferably, the imidazole epoxy resin compounded octanoate is preferably 2-undecyl imidazole (C11Z) and 2-heptadecylimidazole (C17Z). Among them, due to the presence of bulky side groups in the above two compounds, they can form steric hindrance to the active points (secondary amine groups and tertiary amine groups) on the imidazole molecules and reduce their reactivity, making them have a certain latency and maintaining stable fluidity at low temperatures. In addition, since they have long-chain alkyl groups, they have better adhesion. In a preferred embodiment, the content of imidazole resin contained in the inner layer adhesive is 17% to 100% of the weight of the main agent. In another preferred embodiment, the compounded octanoate is preferably zinc octanoate, and the content of zinc octanoate is 1% to 5% of the weight of the main agent.
[0023] More preferably, in order to ensure the heat resistance and structural strength of the metal composite film 1 and to improve the efficiency of the mutual compounding of the layers in the metal composite film 1, a high-quality metal composite film 1 is produced with high efficiency, wherein: the curing agent is an isocyanate curing agent, and the catalyst is an organic tin catalyst, and: the organic tin catalyst contains dibutyltin dilaurate and stannous octoate in a weight ratio of 7:3; and / or the content of the organic tin catalyst is 0.03 to 0.5wt% based on the total weight of the main agent. In a preferred embodiment, the active temperature of the catalyst is 90°C to 110°C. In another preferred embodiment, the inner adhesive layer is formed by heating and curing the inner adhesive liquid at a temperature of 175°C to 195°C for 1 minute. In another preferred embodiment, the curing agent is an epoxy curing agent, and based on the total weight of the epoxy curing agent, the catalyst includes: 8 to 45 wt% of a special amine catalyst, preferably 25 wt%, or 8 to 45 wt% of amidine nitrogen-containing organic matter, preferably 25 wt%, or 8 to 45 wt% of imidazole epoxy resin compound caprylate, preferably 25 wt%, but not limited to this.
[0024] Preferably, in order to improve the corrosion resistance of the metal composite film 1 to prevent the electrolyte from being exposed, to improve the bonding strength of each layer to avoid delamination, or to provide a certain support performance to avoid damage to the intermediate metal layer 2, such as Figure 2As shown, it further includes: an inner anti-corrosion layer 5, formed between the intermediate metal layer 2 and the inner bonding layer 3; or an outer anti-corrosion layer 6, formed on one side of the intermediate metal layer 2, so that the intermediate metal layer 2 is located between the outer anti-corrosion layer 6 and the inner bonding layer 3; or an outer bonding layer 7, formed on one side of the intermediate metal layer 2, so that the intermediate metal layer 2 is located between the outer bonding layer 7 and the inner bonding layer 3; or an outer base resin layer 8, formed on one side of the intermediate metal layer 2, so that the intermediate metal layer 2 is located between the outer base resin layer 8 and the inner bonding layer 3. In a preferred embodiment, the metal composite film 1 is formed by bonding and compounding a plurality of layered structures in sequence along the thickness direction. Specifically, it includes, in sequence from the side away from the electrolyte to the side close to the electrolyte, an outer base resin layer 8, an outer bonding layer 7, an outer anti-corrosion layer 6, an intermediate metal layer 2, an inner anti-corrosion layer 5, an inner bonding layer 3, and a hot-melt resin layer 4.
[0025] Better yet, in the inner adhesive layer 3, through the synergistic effect of the selected main agent, curing agent, and catalyst, the heat resistance of the inner adhesive layer 3, the liquid heat sealing performance of the electrolyte after heat sealing, and the insulation performance of the battery to the outer packaging material can be significantly improved. In addition, by adding the catalyst, the time required for the aging of the inner adhesive layer 3 and the hot melt resin layer 4 during compounding can be greatly reduced, thereby greatly improving the efficiency of lithium-ion battery processing and reducing costs.
[0026] The following describes the effect of the composition of the inner adhesive layer 3 on the performance and preparation efficiency of the metal composite film 1. The inner adhesive layer 3 is formed by curing the inner adhesive liquid. When the curing agent contained therein is an epoxy curing agent, the heat deformation temperature of the inner adhesive layer 3 after the cross-linking reaction will be increased, so that it has higher heat resistance, and the electrical insulation performance and mechanical properties of the metal composite film 1 are significantly improved.
[0027] In addition, in the curing system where the inner layer adhesive liquid is composed of: ① organic fluorine resin, ② acid-modified polypropylene, ③ epoxy curing agent, and ④ amidine nitrogen-containing organic matter, when the catalyst is an amidine compound, because it has a double heterocyclic structure and contains two nitrogen atoms, and Na is sp3 hybridized and Nc is sp2 hybridized, and both have a pair of exposed lone pairs of electrons, the sp2 hybrid orbital of Nc and the sp2 orbital of Cb will form a heavy bond, so that the two adjacent nitrogen atoms show a synergistic effect. This structure determines that it has strong alkalinity, and the strong alkaline structure has a nucleophilic effect and can promote the reaction, so as to improve the efficiency of compounding between the inner layer adhesive layer 3 and the hot melt resin layer 4.
[0028] In addition, in the curing system of the inner layer adhesive liquid composed of: ① organic fluorine resin, ② acid-modified polypropylene, ③ epoxy curing agent, and ④ imidazole epoxy resin compounded with octanoate, first, in the initial stage of the curing reaction, the epoxy group, the acid anhydride, and the octanoate generate coordination ions and alternately open the epoxy ring; then, the octanoic acid anion dissociated from the octanoate reacts with the epoxy group and initiates anionic curing. Among them, imidazole is a five-membered ring containing two nitrogen atoms, one of which constitutes a secondary amine and the other constitutes a tertiary amine. Therefore, it can be understood that its curing of epoxy resin can be divided into the following two stages: the active hydrogen on the secondary amine reacts with the epoxy group; and it can also use the tertiary nitrogen atom and, like the tertiary amine, act as an anionic polymerization curing agent to catalyze the homopolymerization reaction of the epoxy resin to cure the epoxy resin, and make it have excellent heat resistance and mechanical properties after curing. Specifically, since imidazole epoxy resin can catalyze the ring-opening polymerization of epoxy groups, linear molecules can be formed into network macromolecules and the degree of cross-linking can be improved.
[0029] In addition, in the curing system of the inner layer adhesive liquid composed of: ① organic fluorine resin, ② acid-modified polypropylene, ③ isocyanate curing agent, and ④ organic tin catalyst, the organic tin compound can coordinate with the isocyanate group and polarize the NCO chemical bond, thereby making the positively charged carbon atoms in the isocyanate molecule more active. When the inner layer adhesive layer 3 and the hot-melt resin layer 4 are compounded, the time required for the curing and cross-linking reaction between the two is shorter and the reaction is more complete.
[0030] <<The following is a description of a method for forming the metal composite film 1 of the present invention>>
[0031] The metal composite film 1 includes, in order of its stacking direction: an outer base resin layer 8, an outer adhesive layer 7, an outer anti-corrosion layer 6, an intermediate metal layer 2, an inner anti-corrosion layer 5, an inner adhesive layer 3, and a hot-melt resin layer 4. The formation method thereof is shown in the following steps S1 to S5.
[0032] (S1) First, a corona treatment is applied to the side of the outer substrate resin layer 8 that will contact the outer adhesive layer 7, and an anti-corrosion liquid is applied to both sides of the intermediate metal layer 2 to form an outer anti-corrosion layer 6 and an inner anti-corrosion layer 5, respectively. In a preferred embodiment, the outer substrate resin layer 8 is a biaxially oriented nylon with a thickness of 25 μm. In another preferred embodiment, the intermediate metal layer 2 is an aluminum alloy foil with a surface contact angle of 15° and a thickness of 40 μm after annealing and degreasing. In another preferred embodiment, the anti-corrosion liquid contains chromium nitrate, phosphoric acid, nitric acid, chromium fluoride and polyacrylic acid (PAA) in a weight ratio of 58:4:0.7:5:3; and / or the chromium content in the outer anti-corrosion layer 6 or the inner anti-corrosion layer 5 is 15 mg / m 2 .
[0033] (S2) Then, an outer adhesive liquid is coated on the outer anti-corrosion layer 6 and dried to form an outer adhesive layer 7. In a preferred embodiment, the outer adhesive liquid is obtained by mixing a non-crystalline polyester polyol with a weight average molecular weight of 5000, a Tg of 50°C, and a hydroxyl value of 25 mg KOH / g; and a non-crystalline polyester polyol with a weight average molecular weight of 20,000, a Tg of -17°C, and a hydroxyl value of 8 mg KOH / g in a weight ratio of 3:2, and adding toluene diisocyanate (TDI). In another preferred embodiment, in the outer adhesive liquid, the ratio of NCO content to OH content is 6.2. In another preferred embodiment, the thickness of the outer adhesive layer 7 is 3 μm, but is not limited thereto.
[0034] (S3) Compounding the outer base resin layer 8 with the outer adhesive layer 7. In a preferred embodiment, the outer base resin layer 8 is compounded with the side of the intermediate metal layer 2 formed with the outer anti-corrosion layer 6 by a dry compounding method. In another preferred embodiment, after the outer adhesive layer 7 and the outer base resin layer 8 are compounded, an aging treatment is performed at a temperature of 80° C. for 3 days.
[0035] (S4) An inner layer adhesive liquid is applied to the side of the intermediate metal layer 2 where the inner anti-corrosion layer 5 is formed, and the inner layer adhesive layer 3 is formed by drying the inner layer adhesive liquid. In a preferred embodiment, the inner layer adhesive liquid contains one or more of: organic fluorine resin, acid-modified polypropylene, epoxy curing agent, amidine compound, nitrogen-containing organic compound, special amine accelerator, imidazole epoxy resin compound octanoate, isocyanate curing agent, and organic tin catalyst. In another preferred embodiment, the hydroxyl value of the organic fluorine resin is 80mgoH / g and Tg is 37°C; in the epoxy curing agent, the ratio of the epoxy group content to the COOH content is 3.73; or the isocyanate curing agent is IPDI. In another preferred embodiment, the inner layer adhesive liquid is prepared by mixing the inner layer raw material and the solvent, and preferably, methylcyclohexane and butanone in a weight ratio of 8:2 are stirred and mixed to obtain the inner layer adhesive liquid. In another preferred embodiment, the thickness of the inner adhesive layer 3 is 3 μm.
[0036] ( S5 ) Then, at a temperature of 100° C. and a pressure of 0.4 MPA, the heat-welding resin layer 4 and the inner adhesive layer 3 are bonded together and heat-treated at a temperature of 190° C. for 1 minute to form a metal composite film 1 .
[0037] The following is a description of the method for measuring the performance parameters of the metal composite film 1.
[0038] (1) 120℃ high temperature heat seal strength test:
[0039] First, a metal composite film 1 sample with a length of 200 mm in the MD direction and a length of 76 mm in the TD direction was cut, and the metal composite film 1 sample was folded in half along the MD direction and heat-sealed in the MD direction, wherein the heat-sealing conditions were: heat-sealing the metal composite film 1 sample at a heat-sealing temperature of 190° C. and a heat-sealing pressure of 1.0 MPa for 3 seconds.
[0040] Next, after the heat sealing is completed, three samples with a width of 15 mm are cut from the middle position of the metal composite film 1 sample, wherein the cutting line and the heat sealing line are perpendicular to each other.
[0041] Next, the stretching machine was turned on, and the chuck distance was set to 50 mm, the stretching speed was set to 300 mm / min, the measuring stroke was set to 30 mm, and the temperature was set to 120° C., wherein the heat seal strength test result was taken as the maximum value of the entire stroke.
[0042] (2) Parallelism test:
[0043] This test simulates the packaging seal, and when the seal is torn off, observe whether the PP surface is completely fused together to ensure that the metal composite film 1 will not leak after heat sealing.
[0044] First, a metal composite film 1 sample with a length of 200 mm in the MD direction and a length of 76 mm in the TD direction was cut, and the metal composite film 1 sample was folded in half along the MD direction and heat-sealed in the MD direction, wherein the heat-sealing conditions were: heat-sealing the metal composite film 1 sample at a heat-sealing temperature of 190° C. and a heat-sealing pressure of 1.0 MPa for 3 seconds.
[0045] Next, cut off the metal composite film 1 sample along the upper side of the seal (folded end), and then use scissors to cut off the upper right corner of the sample to make it 45°, leaving an area of not less than 2 / 3. Then tear off the seal along the cut corner of the sample. If both sides of the seal are continuously and evenly white, or one side slightly exposes the aluminum foil, it means that both sides are qualified.
[0046] 《Examples 1 to 4 and Comparative Examples 1 to 2 of the Metal Composite Film 1 are provided below》
[0047] ① The following provides Example 1 of the present invention
[0048] In this embodiment, the metal composite film 1 includes: an outer base resin layer 8 (25 μm), an outer adhesive layer 7 (3 μm), an outer anti-corrosion layer 6, an intermediate metal layer 2, an inner anti-corrosion layer 5, an inner adhesive layer 3, and a heat-melting resin layer 4 (40 μm) in order along its stacking direction. The outer base resin layer 8 is a biaxially oriented nylon film with a thickness of 25 μm; the intermediate metal layer 2 is an 8021 series aluminum material with a surface wettability of 68 dyn / cm and a thickness of 35 μm; and the inner anti-corrosion layer 5 and the outer anti-corrosion layer 6 are formed by coating the anti-corrosion liquid on both sides of the intermediate metal layer 2 and drying it, wherein: the anti-corrosion liquid contains chromium phosphate, nitric acid, and polyacrylic acid resin in a weight ratio of 2:2:1.
[0049] In addition, in this embodiment, the preparation method of the inner layer adhesive liquid is: ① an organic fluorine resin with a Tg of 37°C, a hydroxyl value of 80mgoH / g, and a solid content of 66%, ② anhydrous maleic anhydride modified polypropylene solution, ③ an epoxy curing agent with an epoxy equivalent of 175g / eq, and ④ triethylmethylammonium 2-ethylhexane salt (special amine catalyst) with an active temperature of 99°C are mixed and stirred uniformly to obtain the inner layer adhesive liquid. In addition, the inner layer adhesive liquid is applied to the side of the inner anti-corrosion layer 5 relative to the intermediate metal layer 2, and is dried to form an inner layer adhesive layer 3 with a thickness of 2μm.
[0050] In addition, when the inner adhesive layer 3 and the hot melt resin layer 4 are compounded, one side of the hot melt resin layer 4 is first subjected to corona treatment to form a bonding surface, and then the inner adhesive layer 3 and the bonding surface of the hot melt resin layer 4 with a thickness of 40 μm are thermally compounded at a temperature of 100° C., and then an aging treatment is performed at a temperature of 180° C. for 1 minute to obtain a metal composite film 1. Among them, the metal composite film 1 of Example 1 is subjected to a heat sealing strength test at 120° C., and the metal composite film 1 is placed in a hot box at 120° C. for 5 minutes, and the chuck distance is set to 50 mm, the tensile speed is set to 300 mm / min, and the measurement stroke is set to 30 mm, wherein: the heat sealing strength of the metal composite film 1 is 50N.
[0051] ② The following provides Example 2 of the present invention
[0052] The difference between this embodiment and embodiment 1 is that the inner layer adhesive solution includes ① an organic fluorine resin with a Tg of 37°C, a hydroxyl value of 80mgoH / g, and a solid content of 66%, ② an anhydrous maleic anhydride modified polypropylene solution, ③ an epoxy curing agent with an epoxy equivalent of 175g / eq, and ④ a phenol salt of 1,8-diazabicyclo[5.4.0]undecene-7 (amidine nitrogen-containing organic matter) with an active temperature of 80°C. Among them: the heat seal strength of the metal composite film 1 of embodiment 2 at 120°C is 53N.
[0053] ③ The following provides Example 3 of the present invention
[0054] The difference between this embodiment and embodiment 1 is that: the inner layer adhesive solution includes ① an organic fluorine resin with a Tg of 37°C, a hydroxyl value of 80mgoH / g, and a solid content of 66%, ② anhydrous maleic anhydride modified polypropylene solution, ③ an epoxy curing agent with an epoxy equivalent of 175g / eq, and ④ 1-benzyl-2-phenylimidazole or 2-ethyl-4-methylimidazole (imidazole-type epoxy resin) with an active temperature of 105°C and a compound octanoate (zinc octanoate). Among them: the heat sealing strength of the metal composite film 1 of embodiment 3 at 120°C is 60N.
[0055] ④ The following provides Example 4 of the present invention
[0056] The difference between this embodiment and embodiment 1 is that: the inner layer adhesive liquid includes ① an organic fluorine resin with a Tg of 37°C, a hydroxyl value of 80mgoH / g, and a solid content of 66%, ② anhydrous maleic anhydride modified polypropylene solution, ③ an aliphatic polyisocyanate (IPDI trimer) (isocyanate curing agent) with an effective NCO content of 20% and a free IPDI monomer of less than 0.5%, and ④ an organic tin catalyst compounded with dibutyltin dilaurate and stannous octoate in a weight ratio of 7:3. Among them: the heat sealing strength of the metal composite film 1 of embodiment 4 at 120°C is 57N.
[0057] ⑤ The following provides Example 5 of the present invention
[0058] The difference between this embodiment and embodiment 1 is that: the inner layer adhesive liquid includes ① Lumiflon LF910LM with a Tg of 37°C, a hydroxyl value of 80mgoH / g, and a solid content of 66%, an organic fluorine resin obtained by mixing with LF600x, ② anhydrous maleic anhydride modified polypropylene solution, ③ an epoxy curing agent with an epoxy equivalent of 175g / eq, and ④ a catalyst prepared by using triethylmethylammonium 2-ethylhexane salt (special amine catalyst) with an active temperature of 99°C and 1,8-diazabicyclo[5.4.0]undecene-7 phenolate (amidine nitrogen-containing organic matter) with an active temperature of 80°C in a weight ratio of 1:1. Among them: the heat seal strength of the metal composite film 1 of embodiment 5 at 120°C is 61N.
[0059] ⑥ The following provides Example 6 of the present invention
[0060] The difference between this embodiment and embodiment 1 is that: the inner layer adhesive liquid includes ① an organic fluorine resin obtained by mixing Lumiflon LF910LM with a Tg of 37°C, a hydroxyl value of 80mgoH / g, and a solid content of 66% and LF600x, ② an anhydrous maleic anhydride modified polypropylene solution, ③ an isocyanate curing agent obtained by mixing aliphatic polyisocyanate (IPDI trimer) (isocyanate curing agent) with an effective NCO content of 20% and free IPDI monomer less than 0.5% and Desmodur (isocyanate) in a weight ratio of 5:2, and ④ an organic tin catalyst compounded with dibutyltin dilaurate and stannous octoate in a weight ratio of 7:3. Among them: the heat sealing strength of the metal composite film 1 of embodiment 6 at 120°C is 58N.
[0061] ⑦ The following provides a comparative example 1 of the present invention
[0062] The difference between this comparative example and Example 1 is that the inner layer adhesive liquid comprises ① an anhydrous maleic anhydride modified polypropylene solution having a weight average molecular weight of 250,000, a melting point of 85°C, and an acid value of 2, and ② an epoxy curing agent having an epoxy equivalent of 175 g / eq, and the ratio of the carboxyl content (COOH value) contained in the anhydrous maleic anhydride modified polypropylene solution to the epoxy content contained in the epoxy curing agent is: epoxy / COOH=3.73.
[0063] In addition, in the process of compounding the heat-melting resin layer 4, the inner adhesive layer 3 and the bonding surface of the heat-melting resin layer 4 with a thickness of 40 μm are firstly heat-compounded at a temperature of 90° C., and then aged at a temperature of 80° C. for 7 days to obtain the metal composite film 1. Among them: the heat sealing strength of the metal composite film 1 of Comparative Example 1 at 120° C. is 20N.
[0064] ⑧ The following provides a comparative example 2 of the present invention
[0065] The difference between this comparative example and Example 1 is that the inner layer adhesive liquid comprises ① an anhydrous maleic anhydride modified polypropylene solution having a weight average molecular weight of 250,000, a melting point of 85°C, and an acid value of 2, and ② an aliphatic polyisocyanate (IPDI trimer) (isocyanate curing agent) having an effective NCO content of 20% and a free IPDI monomer of less than 0.5%, and the ratio of the carboxyl content (COOH value) contained in the anhydrous maleic anhydride modified polypropylene solution to the NCO content contained in the isocyanate curing agent is: NCO / COOH=3.6.
[0066] In addition, in the process of compounding the heat-melting resin layer 4, the inner adhesive layer 3 and the bonding surface of the heat-melting resin layer 4 with a thickness of 40 μm are firstly heat-compounded at a temperature of 90° C., and then aged at a temperature of 80° C. for 7 days to obtain the metal composite film 1. Among them: the heat sealing strength of the metal composite film 1 of Comparative Example 2 at 120° C. is 16N.
[0067] As shown in Table 1 below, the composition and performance parameters of the metal composite film 1 of Examples 1 to 4 and Comparative Examples 1 to 2 are summarized, from which it can be seen that: Examples 1 to 4 limit the types of the main agent, curing agent, and catalyst contained in the inner adhesive liquid, so that the inner adhesive layer 3 and the hot melt resin layer 4 can have excellent heat resistance and structural strength after being composited, and are not prone to relative separation and electrolyte penetration. In addition, the aging time of the present invention is greatly shortened, so that the production capacity can be increased while maintaining the performance and safety of the lithium-ion battery to meet the needs of industrial production and the market.
[0068] Table 1 Arrangement results of Examples 1 to 4 and Comparative Examples 1 to 2
[0069]
[0070]
[0071] Another object of the present invention is to provide a lithium ion battery, wherein Figure 3 As shown, it comprises: a metal composite film 1, which defines a containing space 9 inside, so as to selectively contain electrolyte, wherein: the metal composite film 1 comprises: an intermediate metal layer 2; an inner adhesive layer 3, formed on one side of the intermediate metal layer 2, wherein the inner adhesive layer 3 comprises: a main agent, comprising: one or more of organic fluorine resin and acid-modified polypropylene; a curing agent, comprising: one or more of epoxy curing agent and isocyanate curing agent; and a catalyst, comprising: one or more of special amine catalyst, amidine nitrogen-containing organic matter, imidazole epoxy resin compound octanoate, and organic tin catalyst; and a hot-melt resin layer 4, formed on one side of the inner adhesive layer 3, so that the inner adhesive layer 3 is located between the intermediate metal layer 2 and the hot-melt resin layer 4, and the hot-melt resin layer 4 is closer to the containing space 9 than the inner adhesive layer 3. In addition, since the material selection and composition ratio of each component in this embodiment have been described in detail in the composition of the metal composite film 1 above, no further description is given here.
[0072] The effect of the present invention relative to the prior art is that the present invention limits the material selection of the main agent, curing agent, and catalyst in the composition of the inner adhesive layer 3, so that a synergistic effect is produced between them to strengthen the bonding strength of the cross-linking curing, and greatly reduce the time required for aging to meet the needs of industrial production. In addition, by limiting the composition of the inner adhesive layer 3, the metal composite film 1 provided by the present invention can have excellent corrosion resistance, packaging, high temperature resistance, durability, insulation, electrochemical reaction stability, safety of use, and peeling strength, so that during the charging and discharging process of the lithium-ion battery, when the temperature of the battery rises, the metal composite film 1 can still maintain its structural strength without stratification, and avoid electrolyte penetration or leakage.
[0073] However, what is described above is only a preferred embodiment of the present invention, but it cannot be used to limit the patent protection scope of the present invention; therefore, all simple equivalent changes and modifications made according to the patent protection scope of the present invention and the contents of the specification still fall within the patent protection scope of the present invention.
Claims
1. A metal composite film, characterized in that: include: Intermediate metal layer; An inner bonding layer is formed on one side of the intermediate metal layer, wherein the inner bonding layer comprises: A main agent, comprising: one or more of an organic fluorine resin and an acid-modified polypropylene; A curing agent, comprising: one or more of an epoxy curing agent and an isocyanate curing agent; and Catalysts, including: one or more of special amine catalysts, amidine nitrogen-containing organic compounds, imidazole epoxy resin compound octanoate, and organic tin catalysts; and The heat-welding resin layer is formed on one side of the inner adhesive layer so that the inner adhesive layer is located between the intermediate metal layer and the heat-welding resin layer.
2. The metal composite film according to claim 1, characterized in that: The curing agent is an epoxy curing agent, and the catalyst is a special amine catalyst; or The curing agent is an epoxy curing agent, and the catalyst is an amidine-type nitrogen-containing organic compound; or The curing agent is an epoxy curing agent, and the catalyst is imidazole epoxy resin compound octanoate; or The curing agent is an isocyanate curing agent, and the catalyst is an organotin catalyst.
3. The metal composite film according to claim 1, characterized in that: The epoxy curing agent is one or more selected from the group consisting of the following materials: bisphenol A epoxy resin, bisphenol F epoxy resin, phenol novolac epoxy resin, o-cresol novolac epoxy resin, trisphenol methane epoxy resin, tetraphenol ethane epoxy resin, polyphenol glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin, and glycidyl ester epoxy resin; The special amine catalyst is one or more selected from the group consisting of the following materials: triethylmethylammonium 2-ethylhexane salt, tetramethylammonium chloride, and triethylenediamine; The amidine nitrogen-containing organic compound is one or more selected from the group consisting of the following materials: phenol salt of 1,8-diazabicyclo[5.4.0]undecene-7, 1,5-diazabicyclo[4.3.0]non-5-ene, and triazoamidine; The imidazole epoxy resin compound octanoate is one or more selected from the group consisting of the following materials: 2-methylimidazole (2MZ), 2-ethyl-4-methylimidazole (2E4MZ), 2-phenyl-4-methylimidazole (2P4MZ), 1-benzyl-2-phenylimidazole (1B2PZ), 2-phenylimidazole (2PZ), 2-undecylimidazole (C11 Z), 2-heptadecylimidazole (C17Z), 1-aminoethyl-2-methylimidazole (AMZ), 2-methylimidazole-trimellitic anhydride chloride (2MI-T), and 2-ethyl-4-methylimidazole-trimellitic anhydride chloride (EMI-T); The isocyanate curing agent is one or more selected from the group consisting of the following materials: aliphatic polyisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate; and The organotin catalyst is one or more selected from the group consisting of the following materials: dibutyltin oxide, dibutyltin dibutyrate, dimethyltin dibutyrate, dioctyltin dibutyrate, dibutyltin diacetate, dimethyltin diacetate, dioctyltin diacetate, dimethyltin dilaurate, dibutyltin dilaurate, stannous octoate, stannous oleate, and dibutyltin didodecylsulfide.
4. The metal composite film according to claim 1, characterized in that: The hydroxyl value of the organic fluorine resin is 20mgoH / g to 80mgoH / g; and / or The weight ratio of the organic fluorine resin to the acid-modified polypropylene is 40:
100.
5. The metal composite film according to claim 1, characterized in that The curing agent is an isocyanate curing agent, and the catalyst is an organotin catalyst, and: The organotin catalyst comprises dibutyltin dilaurate and stannous octoate in a weight ratio of 7:3; and / or Based on the total weight of the main agent, the content of the organic tin catalyst is 0.03 to 0.5 wt %.
6. The metal composite film according to claim 1, characterized in that The active temperature of the catalyst is 90°C to 110°C.
7. The metal composite film according to claim 1, characterized in that The inner adhesive layer is formed by curing the inner adhesive liquid at a temperature of 175° C. to 195° C. for 1 minute.
8. The square metal composite film according to claim 1, characterized in that: The curing agent is an epoxy curing agent, and the catalyst includes, based on the total weight of the epoxy curing agent, 8 to 45 wt% of a special amine catalyst, or 8 to 45 wt% of amidine nitrogen-containing organic matter, or 8 to 45 wt% of imidazole epoxy resin compound caprylate.
9. The metal composite film according to claim 1, characterized in that After the metal composite film is stored in a hot box at 120° C. for 5 minutes, the heat sealing strength thereof is ≥50N.
10. The metal composite film according to claim 1, characterized in that It also includes: an inner anti-corrosion layer formed between the intermediate metal layer and the inner bonding layer; or an outer anti-corrosion layer formed on one side of the intermediate metal layer so that the intermediate metal layer is located between the outer anti-corrosion layer and the inner bonding layer; or an outer adhesive layer formed on one side of the intermediate metal layer so that the intermediate metal layer is located between the outer adhesive layer and the inner adhesive layer; or The outer base resin layer is formed on one side of the intermediate metal layer so that the intermediate metal layer is located between the outer base resin layer and the inner adhesive layer.
11. A lithium ion battery, characterized in that: Contains: metal composite film, its internal boundary A containing space is provided to selectively contain electrolyte, wherein: the metal composite membrane comprises: Intermediate metal layer; An inner bonding layer is formed on one side of the intermediate metal layer, wherein the inner bonding layer comprises: A main agent, comprising: one or more of an organic fluorine resin and an acid-modified polypropylene; A curing agent, comprising: one or more of an epoxy curing agent and an isocyanate curing agent; and Catalysts, including: one or more of special amine catalysts, amidine nitrogen-containing organic compounds, imidazole epoxy resin compound octanoate, and organic tin catalysts; and The hot-melt resin layer is formed on one side of the inner adhesive layer, so that the inner adhesive layer is located between the intermediate metal layer and the hot-melt resin layer, and the hot-melt resin layer is closer to the accommodating space than the inner adhesive layer.
12. The lithium ion battery according to claim 11, characterized in that: The curing agent is an epoxy curing agent, and the catalyst is a special amine catalyst; or The curing agent is an epoxy curing agent, and the catalyst is an amidine-type nitrogen-containing organic compound; or The curing agent is an epoxy curing agent, and the catalyst is imidazole epoxy resin compound octanoate; or The curing agent is an isocyanate curing agent, and the catalyst is an organotin catalyst.
13. The lithium ion battery according to claim 11, characterized in that: The epoxy curing agent is one or more selected from the group consisting of the following materials: bisphenol A epoxy resin, bisphenol F epoxy resin, phenol novolac epoxy resin, o-cresol novolac epoxy resin, trisphenol methane epoxy resin, tetraphenol ethane epoxy resin, polyphenol glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin, and glycidyl ester epoxy resin; The special amine catalyst is one or more selected from the group consisting of the following materials: triethylmethylammonium 2-ethylhexane salt, tetramethylammonium chloride, and triethylenediamine; The amidine nitrogen-containing organic compound is one or more selected from the group consisting of the following materials: phenol salt of 1,8-diazabicyclo[5.4.0]undecene-7, 1,5-diazabicyclo[4.3.0]non-5-ene, and triazoamidine; The imidazole epoxy resin compound octanoate is one or more selected from the group consisting of the following materials: 2-methylimidazole (2MZ), 2-ethyl-4-methylimidazole (2E4MZ), 2-phenyl-4-methylimidazole (2P4MZ), 1-benzyl-2-phenylimidazole (1B2PZ), 2-phenylimidazole (2PZ), 2-undecylimidazole (C11 Z), 2-heptadecylimidazole (C17Z), 1-aminoethyl-2-methylimidazole (AMZ), 2-methylimidazole-trimellitic anhydride chloride (2MI-T), and 2-ethyl-4-methylimidazole-trimellitic anhydride chloride (EMIT); The isocyanate curing agent is one or more selected from the group consisting of the following materials: aliphatic polyisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate; and The organotin catalyst is one or more selected from the group consisting of the following materials: dibutyltin oxide, dibutyltin dibutyrate, dimethyltin dibutyrate, dioctyltin dibutyrate, dibutyltin diacetate, dimethyltin diacetate, dioctyltin diacetate, dimethyltin dilaurate, dibutyltin dilaurate, stannous octoate, stannous oleate, and dibutyltin didodecylsulfide.
14. The lithium ion battery according to claim 11, characterized in that: The hydroxyl value of the organic fluorine resin is 20mgoH / g to 80mgoH / g; and / or The weight ratio of the organic fluorine resin to the acid-modified polypropylene is 40:
100.
15. The lithium ion battery according to claim 11, characterized in that: The curing agent is an isocyanate curing agent, and the catalyst is an organotin catalyst, and: The organotin catalyst comprises dibutyltin dilaurate and stannous octoate in a weight ratio of 7:3; and / or Based on the total weight of the main agent, the content of the organic tin catalyst is 0.03 to 0.5 wt %.
16. The lithium ion battery according to claim 11, characterized in that: The active temperature of the catalyst is 90°C to 110°C.
17. The lithium ion battery according to claim 11, characterized in that: The inner adhesive layer is formed by curing the inner adhesive liquid at a temperature of 175° C. to 195° C. for 1 minute.
18. The lithium ion battery according to claim 11, characterized in that: The curing agent is an epoxy curing agent, and the catalyst includes, based on the total weight of the epoxy curing agent, 8 to 45 wt% of a special amine catalyst, or 8 to 45 wt% of amidine nitrogen-containing organic matter, or 8 to 45 wt% of imidazole epoxy resin compound caprylate.
19. The lithium ion battery according to claim 11, characterized in that: After the metal composite film is stored in a hot box at 120° C. for 5 minutes, the heat sealing strength thereof is ≥50N.
20. The lithium ion battery according to claim 11, characterized in that: It also includes: an inner anti-corrosion layer formed between the intermediate metal layer and the inner bonding layer; or an outer anti-corrosion layer formed on one side of the intermediate metal layer so that the intermediate metal layer is located between the outer anti-corrosion layer and the inner bonding layer; or an outer adhesive layer formed on one side of the intermediate metal layer so that the intermediate metal layer is located between the outer adhesive layer and the inner adhesive layer; or The outer base resin layer is formed on one side of the intermediate metal layer so that the intermediate metal layer is located between the outer base resin layer and the inner adhesive layer.
